2007
DOI: 10.1523/jneurosci.2969-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

FMRP Phosphorylation Reveals an Immediate-Early Signaling Pathway Triggered by Group I mGluR and Mediated by PP2A

Abstract: Fragile X syndrome is a common form of inherited mental retardation and is caused by loss of fragile X mental retardation protein (FMRP), a selective RNA-binding protein that influences the translation of target messages. Here, we identify protein phosphatase 2A (PP2A) as an FMRP phosphatase and report rapid FMRP dephosphorylation after immediate group I metabotropic glutamate receptor (mGluR) stimulation (Ͻ1 min) in neurons caused by enhanced PP2A enzymatic activity. In contrast, extended mGluR activation (1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
248
2
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(259 citation statements)
references
References 43 publications
6
248
2
3
Order By: Relevance
“…[46][47][48] The mechanism of how FMRP exerts its translation regulator function is still under investigation, however, previous findings have suggested that phosphorylation plays a role in the FMRP translation regulation function. 8,29,50 Aiming to understand if the FMRP phosphorylation results in any potential binding affinity difference to the G-quadruplex forming Shank1 RNA, we employed the previously created phosphorylated mimic form of FMRP isoform 1, FMRP S500D, in which serine 500 was mutated to aspartic acid. 29,50,51 The FMRP ISO1 and FMRP S500D were recombinantly expressed in E. coli cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[46][47][48] The mechanism of how FMRP exerts its translation regulator function is still under investigation, however, previous findings have suggested that phosphorylation plays a role in the FMRP translation regulation function. 8,29,50 Aiming to understand if the FMRP phosphorylation results in any potential binding affinity difference to the G-quadruplex forming Shank1 RNA, we employed the previously created phosphorylated mimic form of FMRP isoform 1, FMRP S500D, in which serine 500 was mutated to aspartic acid. 29,50,51 The FMRP ISO1 and FMRP S500D were recombinantly expressed in E. coli cells.…”
Section: Resultsmentioning
confidence: 99%
“…6,7 FMRP normally represses the translation of its mRNA targets, the release of this repression being coupled with its dephosphorylation in response to an activation signal, which results in a burst of local protein synthesis. 8,9 In fragile X syndrome neurons, however, a subset of dendritic proteins synthesis is constitutively elevated due to the lack of FMRP even in the absence of an activation signal. 10 FMRP has been shown to use its RGG box domain to bind mRNA targets that form G-quadruplex structures.…”
Section: Introductionmentioning
confidence: 99%
“…While the functional requirement for CKI-dependent dFMR1 phosphorylation is as of yet not understood, there is considerable evidence that the phosphorylation state of FMRP may actually determine its role in translation. Biochemical data demonstrate that most FMRP in granules is in the phosphorylated state while FMRP in the polysome fraction is dephosphorylated (Ceman et al 2003), suggesting a mechanism to switch state from an activator to a repressor, and an important regulatory role for kinases that phosphorylate FMRP (Narayanan et al 2007(Narayanan et al , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have shown that phosphorylation of FMRP at serine 499 in mouse (500 in human) results in translational repression [77][78][79][80][81]. Dephosphorylation of FMRP by PP2A in response to mGlu1/5 activation removes translational repression [82]. FMRP can also be ubiquitinated in response to mGlu1/5 activation [83], and this mechanism can occur locally within dendrites and at synapses [84].…”
Section: Mechanisms Of Fmrp-mediated Regulation Of Mrna Translation Imentioning
confidence: 99%